Characterization of the Eucalyptus ( E. Globulus) Leaves Oil - Khan, Astaq Mohal; Khatun, Seatara; Hossain, MK; Rahman, M L (Journal of the Bangladesh Chemical Society, 2012)
Studies were carried out on the characterization of Eucalyptus globulus leaves oil. It is found that Eucalyptus globulus tree bears a lot of leaves which are grown under the soil texture and climatic condition of Bangladesh contain a fair amount of pale yellow coloured volatile oil. The oil of the leaves were extracted by hydro distillation method during the month of July to December. The highest yield (3.5%) of the oil was obtained from the maturity leaves of the tree in the month of July and the lowest yield (0.08) in the month of December. Physico-chemical characteristics of the extracted oil like saponification value, acid value, iodine value, specific gravity, refractive index, optical rotation and separation of lipid classes were studied by the conventional methods and the results suggested that the oil can be used suitably for the preparation of pharmaceutical and industrial products. DOI: http://dx.doi.org/10.3329/jbcs.v25i1.11780 Journal of Bangladesh Chemical Society, Vol. 25(2),97-100, 2012